PENDAMPINGAN INOVASI DIGITALISASI ABSENSI GURU BERBASIS QR CODE SEBAGAI UPAYA PENGUATAN TATA KELOLA DAN KARAKTER DISIPLIN DI SMP DARUL LUGHAH WAL KAROMAH - Wanda Faris Wahyudi; Akmal Mundiri (DEVELOPMENT: Journal of Community Engagement, 2026)
This community service aims to help the implementation of the teacher attendance system using QR codes as a way to improve administrative management and teacher discipline attitudes at Darul Lughah Wal Karamah Junior High School. This activity was motivated by the lack of optimal use of the digital attendance system, because most teachers still need help in using the system. The method used is participatory assistance which goes through several stages such as observation, socialization, technical training, use practices, as well as monitoring and evaluation. The results of the activity showed that the mentoring assistance helped teachers better understand how to use the QR code-based attendance system, make the process of recording and collecting attendance data faster, and facilitate attendance monitoring directly and in real time. In addition, the application of this innovation also helps to improve the nature of discipline, responsibility, and professionalism of teachers. Thus, assistance in the implementation of QR Code-based attendance is an effective strategy to support changes towards more digital school governance